Alcohol Induced Acute Kidney Injury in A 13-Year-Old Nigerian Boy; A Case Report - Ajite, Adebukola; Ogundare, Ezra; Oluwayemi, Isaac; Adebisi, Olufemi (British Journal of Healthcare and Medical Research, 2023)
Alcohol misuse has been insinuated to be a cause of acute kidney injury with various patho-mechanisms suggested. We present a case of a 13 year old Nigerian boy who was admitted on account of vomiting of 4 episodes of 24 hours duration, convulsion of several episodes within 3hrs prior to presentation and associated loss of consciousness. He was apparently well until the outset of symptoms which were preceded by ingestion of about 250mls of ‘LORDS’ dry gin containing 43% alcohol mixed with Cocacola.The urinary output was 0.67mls/kg/hr on the first day of admission while the peak serum creatinine value was 1425.2µmol/l. The random blood sugar at admission was 14mmol/l. He was given intravenous fluid 5% Dextrose /saline, intravenous phenytoin, diazepam 5mg, and antibiotic. He had 2 sessions of haemodialysis within 48 hours apart. Subsequently, he regained full consciousness after the first session of dialysis and the creatinine level at discharge was 73µmol/l with urine output of 1.67ml/min/hr. He was co-managed with the Psychiatrist and the duration of admission was 16 days. He is being followed up after discharge at the Paediatric nephrology clinic.